'Optimized route' to synthesize isoelectronic and isostructural Au(iii)- and Pt(ii)-NHC complexes: synthesis, structure, spectral properties, electrochemistry, and molecular docking studies. (5th December 2022) - Maity, Lakshmikanta; Barik, Sahadev; Kisan, Hemanta K.; Jana, Abhimanyu; Isab, Anvarhusein A.; Dinda, Joydev
Abstract : Synthesis, structures, luminescent properties, electrochemistry, and molecular docking of isoelectronic and isostructural Au(iii )- and Pt(ii )-NHC complexes have been described. Abstract : We report the synthesis, structures, luminescent properties, and electrochemistry of gold(iii ) and platinum(ii )-N-heterocyclic carbene complexes. The proligand 1-methyl-2-(pyridylmethyl)imidazo[1, 5- a ]pyridin-4-ylium hexafluorophosphate, (1 ·HPF6 ), and two novel isoelectronic and isostructural complexes, viz. [Au(1 )2 ][PF6 ]3 (2 ), [Pt(1 )2 ][PF6 ]2 (3), were synthesized and characterized by several spectroscopic studies. Finally, the single crystal X-ray diffraction studies established the square planar geometry of both complexes 2 and 3 . The solid state structures of both the square planar complexes revealed two Ccarbene and two Npyridine present in trans fashion around the central metal ions. The complexes showed strong absorbance at ∼350 nm and DFT studies demonstrated the ILCT transition. Both complexes are luminescent at ∼400 nm. DFT and TDDFT studies were performed to gain insights into the experimental findings of solid-state structures and electronic properties. Electrochemical studies of Au(iii )-NHC complex 2 showed two irreversible Au(iii ) → Au(i ) and Au(i ) →Au(0) reductions at −0.75 V and −1.28 V, whereas Pt(ii )-NHC complex 3 revealed Pt(ii /iv ) two-electron reversible oxidation potential at 0.53 V. Molecular docking analysis revealed the highest free binding energy for complex 3 with human-DNA topoisomerase as compared to complex 2 and proligand 1 ·HPF6 . Pharmacokinetics studies revealed the scope of the complexes to be potent drugs.